Dichlorido(furfurylmine-?N)(?6-hexamethylbenzene)ruthenium(II) - Garci, Amine; Thai, Trieu-Tien; Süss-Fink, Georg; Therrien, Bruno (My University, 2011)
The single-crystal x-ray structure anal. of [RuCl2(C12H18)(C5H7NO)] reveals a distorted piano-stool geometry around the RuII atom, with a hexamethylbenzene ligand, two chloride ligands and a furfurylamine ligand, the latter coordinating through the amine group. In the crystal, a dimeric structure is obsd. as a result of N-H···Cl interactions between two symmetry-related mols. Crystallog. data and at. coordinates are given. [on SciFinder(R)]
Keywords: mol structure ruthenium chlorido furfurylamine hexamethylbenzene; crystal structure ruthenium chlorido furfurylamine hexamethylbenzene; hydrogen bond ruthenium chlorido furfurylamine hexamethylbenzene